Maximizing machinery uptime - Geitner, Fred K. (Bloch, Heinz P., 1933- Practical machinery management for process plants, 2006)
The authors use their decades of experience and draw upon real-world examples to demonstrate that the application of their techniques provides a basis for equipment management, uptime maximization, and reduced maintenance costs. The text explores reliability assessment techniques such as Failure Mode, Effect Analysis, and Fault Tree Analysis of commonly encountered rotating machinery. These are all highly effective techniques that the engineer can apply to maximize uptime and thereby maximize production and profitability. *Provides the tools to drastically improve machinery productivity and performance *Bridges the gap between the theory of "reliability engineering" and the practical day-to-day measures that lead to machinery uptime *Authoritative reference for maximizing the uptime of process equipment.